MOSQUITO DISTRIBUTION OF MOSQUITE-DISEASES MALARIA, JAP ANCE ENCEPHALITIS AND FILARIA IN SEVERAL A CENTRAL JAVA AREA - Hasan Boesri; Damar Tri Boewono; Hadi Suwasono; Raharjo Raharjo (Jurnal Penelitian Saintek, 2002)
A study on distribution of Malaria, Filariasis, Japanise encephalitis vectors was conducted in several areas of Central Java in 1998/1999. The result showed that larvae of An. barbirostris, An. subpictus, An. aconitus, An. vagus, An.  maculatus, An. kochi, Lutzia sp,  Cx. vishnui, Cx.pipiens quinquefasciatus,' Cx. gelidus, Lutzia sp  Cx. tritaeniorhynchus, Cx. bitaeniorhynchus and Cx. fuscocephalus werefound in the Rice field. Larvae of Ae. Albopictus and Ar. kucingensis were found in the coconut shell. Larvae of Ae. Albopictus and Malaya sp were found in the Banana leaf axil.  Larvae of Ae. Albopictus, Ae. aegypti and Cx. pipiens quinquefasciatus werefound in the artificial container. Larvae of Ae. poicilius, and Malaya sp were found  in Callocasia leaf axil. Larvae of An. barbirostris, An. vagus, An.  subpictus, An. tessellatus, Cx. vishnui, and Mn. uniformis were found  in the swamp. Larvae of ex. Pipiens quinquefasciatus were found  in the polluted water. Larvae of An.sundaicus, An. subpictus, An. barbirostris and An.  vagus werefound in the tick pond. An. maculatus, Ae. albopictus, and An. vagus larvae werefound in the rock pool. Larvae An. barbirostris, Cx. vishnui, and Cx. bitaeniorhynchus of were found  in the irrigation canal.  Larvae of ex. vishnui, and ex. fuscocephalus  were found  in the Stream pool. An. barbirostris, ex. fragilis, An. vagus, Cx. Vishnui and Cx. bitaeniorhynchus larvae were found  in the pond. Larvae of ex. vishnui were found  in the ground pool. Larvae of Ae. albopictus werefound  in the Bamboo stump. An. nigerrimus, An. peditaeniatus,. An. vagus, An. subpictus, An.  aconitus, An. annularis, An kochi, An. jlavirostris, An.    barbirostris,   An.    indevinitus   An.    tessellatus,   An.maculatus,    Cx. bitaeniorhynchus, ex.  vishnui, ex.  tritaeniorhynchus, Cx. fuscocephalus,  Mn. uniformis, Cx.pipiens quinquefasciatus, Cx. gelidus, Mn. uniformis, Ae. poicilius, Ae. subalbatus, and Ar. kuchingensis were found  in the cattle shelter during night collection. Based on the information mentioned above showed that the higher area  the less  of larvae species.  Each larval species  has  a specific breeding site. This data is usefulfor mosquito'control program.